FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND POLICY PADA PERUSAHAAN NON KEUANGAN DI BEI - Nina Saputri; Merry Susanti (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this research is to determine the effect of company size, ROA, leverage, liquidity and free cash flow on dividend policy on non-financial companies listing on the Indonesia Stock Exchange during the period of 2015-2017. This research uses quantitative methods. This study uses 25 samples that have been selected through a judgmental sampling. The data used is secondary data and processing using eviews 10.0. The results showed that company size, ROA, leverage, liquidity and free cash flow had no effect on dividend policy. This research is expected to provide benefits to assist investment players in determining suitable companies to invest in stocks, especially in non-financial companies and to contribute to the development of current knowledge, particularly in developing theories regarding dividend policy in order to provide improvement (progress) in further research.